1993
DOI: 10.1073/pnas.90.16.7461
|View full text |Cite
|
Sign up to set email alerts
|

Human lung expresses unique gamma-glutamyl transpeptidase transcripts.

Abstract: quencing, and COS cell expression. We demonstrate the existence of a classical yGT cDNA with an unusual 5' untranslated region (UTR) and a full-length open reading frame (ORF) encoding functional enzyme. In addition we characterize a second lung-specific mRNA population, § which is found in great abundance and hybridizes with the 3' half of the full-length yGT transcript. These mRNAs poten-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
3
23
0
1
Order By: Relevance
“…the stability of the fully "mature" ⌬F508 CFTR protein. While using high concentrations of osmolytes may not be clinically desirable, GSNO, a substrate for GGT, an enzyme also expressed in the lung (62), is one potential therapeutic candidate. In this regard, a study of nine CF patients receiving one dose of aerosolized GSNO showed that the compound was safely tolerated (63).…”
Section: Fig 4 Gsno Promotes the Maturation And Function Of ⌬F508mentioning
confidence: 99%
“…the stability of the fully "mature" ⌬F508 CFTR protein. While using high concentrations of osmolytes may not be clinically desirable, GSNO, a substrate for GGT, an enzyme also expressed in the lung (62), is one potential therapeutic candidate. In this regard, a study of nine CF patients receiving one dose of aerosolized GSNO showed that the compound was safely tolerated (63).…”
Section: Fig 4 Gsno Promotes the Maturation And Function Of ⌬F508mentioning
confidence: 99%
“…2). As compared to the truncated group II wt mRNAs described by Wetmore et al [9], type III mRNAs exhibit the sequences corresponding to the region named C and the two bases of the 3' end of the region named B [9]. Further, three point mutations distinguish type III mRNA from group II wt mRNAs.…”
Section: Partial Cloning Of Ggt Type III Mrnamentioning
confidence: 93%
“…3). Because of the presence of the unspliced intron and point mutations, this polypeptide has about 80% homology with the amino acid sequence deduced from wild-type truncated mRNA peptide [9].…”
Section: Partial Cloning Of Ggt Type III Mrnamentioning
confidence: 99%
See 2 more Smart Citations